Improved auxiliary inductive coil connectors in DC boost converters with high voltage gain for renewable energy source applications - Anusak Bilsalam; Nicu Bizon; Phatiphat Thounthong (Institute of Advanced Engineering and Science, 2022)
This study investigates an auxiliary technique for the integration of inductive coil connectors (AIIC) within a single switched DC converter with high voltage gain for renewable energy source applications. The aim is to develop and improve the rate of voltage gain for both coils by using inductive coil connectors (coupling inductance) on the input side that goes through the ratio operator of both inductive coils of the high frequency transformer by having the prototype power circuit operate at a switching frequency 80 kHz. Experimental results show that the output power is at 125 W, output voltage is at 325 V, and input voltage is at 36 V. Furthermore, the duration of change of critical waves of the duty condition was analyzed to confirm that the results were consistent with the proposed technique.